How it went down - Magoon, Kekla (Henry Holt and Company, 2014)
When sixteen-year-old Tariq Johnson is shot to death, his community is thrown into an uproar because Tariq was black and the shooter, Jack Franklin, is white, and in the aftermath everyone has something to say, but no two accounts of the events agree.